Lymphangioma circumscriptum treated with radiofrequency ablation - Silonie Sachdeva (Wolters Kluwer Medknow Publications, 2011)
Lymphangioma circumscriptum (LC), a hamartomatous lymphatic malformation, is a therapeutic challenge for the dermatologist. Various modalities like surgical excision, lasers, and sclerotherapy have been used in the past to treat this notorious skin condition. We report the efficacy of a radiofrequency ablation in a patient with LC. The treatment efficacy of radiofrequency was satisfactory in our patient with no recurrence during 1 year follow-up period. The radiofrequency technique is a safe and economic treatment for management of LC.